ECMDB 2.0: A richer resource for understanding the biochemistry of E. coli. Issue Volume 44:Issue D1(2016) (19th October 2015) - Sajed, Tanvir; Marcu, Ana; Ramirez, Miguel; Pon, Allison; Guo, An Chi; Knox, Craig; Wilson, Michael; Grant, Jason R.; Djoumbou, Yannick; Wishart, David S.
Abstract: ECMDB or the Escherichia coli Metabolome Database (http://www.ecmdb.ca ) is a comprehensive database containing detailed information about the genome and metabolome of E. coli (K-12). First released in 2012, the ECMDB has undergone substantial expansion and many modifications over the past 4 years. This manuscript describes the most recent version of ECMDB (ECMDB 2.0). In particular, it provides a comprehensive update of the database that was previously described in the 2013 NAR Database Issue and details many of the additions and improvements made to the ECMDB over that time. Some of the most important or significant enhancements include a 13-fold increase in the number of metabolic pathway diagrams (from 125 to 1650), a 3-fold increase in the number of compounds linked to pathways (from 1058 to 3280), the addition of dozens of operon/metabolite signalling pathways, a 44% increase in the number of compounds in the database (from 2610 to 3760), a 7-fold increase in the number of compounds with NMR or MS spectra (from 412 to 3261) and a massive increase in the number of external links to other E. coli or chemical resources. These additions, along with many other enhancements aimed at improving the ease or speed of querying, searching and viewing the data within ECMDB should greatly facilitate the understanding of not only the metabolism of E. coli, but also allow the in-depth exploration of its extensive metabolic networks, its many signalling pathways and its essential biochemistry.